Shoe-makers' polyneuropathy in Italy: the aetiological problem. Issue 2 (May 1976) - Abbritti, G; Siracusa, A; Cianchetti, C; Coli, A; Curradi, F; Perticoni, G F; De Rosa, F
Abstract : Since 1957, when the first cases of the so-called shoe-makers' toxic polyneuropathy were reported, nearly 400 cases have been described in the Italian literature. The substance that was considered to be responsible for the disease was triorthocresylphosphate (TOCP) contained in glues, artificial leathers, and some types of paints. However numerous chemical analyses of glues and leathers taken from factories where cases of the disease occurred have shown that in almost all instances little or no TOCP was present. In addition the disease manifests itself more frequently during winter and spring and this is not consistent with the absorption of the causative agent through the skin and/or gastrointestinal tract. In order to clarify the aetiology of the disease 122 workers in the shoe industry affected by toxic polymeuropathy during the period 1971-74 were studied. Workplaces where cases of polyneuropathy had occurred were visited and samples of glues and solvents were taken for chemical analysis. The polyneuropathy chiefly affects workers engaged in glueing and in the cleaning process, but it also affects those who do not have direct contact with glues or solvents. The disease is more common in women (68%) than in men (32%) and, in its more severe form begins with overwhelming prevalence during winter and early spring regardless of the job performed. No direct relationship has been found between the severity of the disease and the number of years of work in the shoe industry or of specific exposure (that is the number of years of work in the activity performed at the onset of the disease). The polyneuropathy is found almost exclusively among workers of the artisam type in small shoe factories, where standards of hygiene are low. Chemical analysis of glues and cleaning fluids collected from five different factories, where 20 cases of polyneuropathy occurred, showed the presence of paraffin hydrocarbons with a low boiling point (pentane, 2-methyl-pentane, 3-methyl-pentane, n-hexane, etc.) in concentrations of more than 80% by weight.